MODERN APPROACHES IN THE FIELD OF SAFETY OF RAILWAY TRANSPORT - Skogarev, I. Ye.; Kobozev, O. Ya.; Zhyzhko, V. V.; Bohomazova, Ye. O. (Science and Transport Progress, 2007)
The article is devoted the actual questions of increase of safety of motion on a railway transport, namely introduction of education-testing programmatic complex. A programmatic complex is given by teaching possibility, verifications of knowledges of workers of railway with subsequent verification of the mastered material, and also possibility of timely organization of handing over of attestations.